The Relationship Between Principals' Patterns of Leadership According to Blanchard and Hersey Theory and The Level of Teacher's Job Satisfaction in the Directory of Education in Amman First Area - Eid, Faten Saleem (Journal of Educational and Psychological Sciences, 2021)
This study aimed at identifying the relationship of leadership pattern with the satisfaction of their teachers in the Directorate of Education in Amman First Area' as well as finding if there are any specialty, secondary school principal pattern, and the interaction between them, The study objectives are to answer the following questions: 1. What are the leadership patterns of the secondary school principals according to Blanchard and Hersey theory?2. What is the extent of job satisfaction among teachers?3. Are there any significant differences for job satisfaction and the secondary school principal pattern concerning teacher specialty and the interaction between them?4. Are there any significant differences for job satisfaction and the leadership pattern of school principal and the interaction between?5. There were differences in satisfaction resulted of the specialty factor, while other differnces resulted of the secondary school principal's leadership pattern and there was no interaction between specialty and the leadership pattern of the principals.The study recommended that:1. There should be concentration on the selling leadership pattern, as well as concentrating on the participation of the teacher in decision making and meet their needs and wells.2. Training the managers on the suitable leadership patterns and develop them vocationally.3. To find out the reasons of the satisfaction of male teacher concerning the teaching process and find the solutions.4. Increase the level of satisfaction for teachers through the enrichment of their spiritual level and support their position in society.5. Performing more studies concerning the leadership pattern and the job satisfaction including the factors not included in this study such as age, marital status, work place, and salary.
Keywords: leadership style; school principals; Blanchard and Hersey Theory; job satisfaction; secondary school teachers